Life-cycle inventory (LCI) analyses of the recycling processes of plastic bottle and film products in Germany and South Africa - Stinnes, Ingo Alexander (Stellenbosch : Stellenbosch University, 2012)
Thesis (M. Ing.) -- University of Stellenbosch, 1995.